An introduction to the internationalization of higher education : essential topics - Arabkheradmand, Ali (University Press of America, 2015)
Internationalization of higher education is a concept that is currently making its way to every corner of the globe. This book aims to provide the reader with an introduction to this subject and explore three of its most fundamental aspects, namely, internationalization at home, internationalization abroad, and internationalization of curriculum.